Patient-reported Outcomes following Elective Surgery for Lumbar Degenerative Disease: Effect of Peri-operative Complications on Outcomes. Issue 1 (April 2016) - Chotai, Silky; Parker, Scott; Sivaganesan, Ahilan; McGirt, Matthew; Cheng, Joseph; Devin, Clinton
Introduction: There is a paradigm shift toward rewarding providers for quality rather than volume. Complications appear to occur at a fairly consistent frequency when looking at large aggregate datasets. Understanding how complications affect long-term patient reported outcomes (PROs), following degenerative lumbar surgery, is vital. Our hypothesis was that 90-day complications would adversely affect long term PROs compared with a cohort that did not experience a complication. Methods 906 consecutive patients undergoing elective surgery for degenerative lumbar disease over a period of four-years were enrolled into a prospective longitudinal registry. PROs: ODI, NRS-Back and leg pain (BP, LP), Quality of life (EQ-5D), and NASS satisfaction questionnaire were recorded at baseline and 12-month follow-up. Complications were divided into major (surgical site infection, hardware failure, new neurological deficit, pulmonary embolism, hematoma and MI) and minor (urinary tract infection, pneumonia and deep venous thrombosis). Results: Thirteen percent (118) of patients developed complications: (major-12% (108) and 8% (68)-minor) within 90-days after surgery. The patients with complications had significantly higher ODI scores at 12-months (29.43 ± 17.7 versus 25.2 ± 18.33, p = 0.02) after surgery. In a multivariable linear regression analysis, after controlling for array of preoperative variables, the occurrence of a major complication was not associated with worsening ODI scores 12-month after surgery. There was no difference in the percent of patients achieving minimal clinically important difference MCID for disability (66% vs 64%), back (55% vs 56%) and leg pain (62% vs 59%), quality of life (19% vs14%) and patient satisfaction rates (82% vs 80%) between those without and with major complications. Conclusion: The occurrence of major complications did not significantly affect the PROs 12-month after surgery. These patients achieve clinically meaningful outcomes and patient satisfaction, as much as those without complication. This information allows a physician to council patients on the fact that a complication creates frustration, cost, and inconvenience, however it does not appear to adversely affect clinically meaningful long-term outcomes and satisfaction.